KONSEP ANAK ANGKAT DALAM PRAKTEK MASYARAKAT KLUET (Analisis Perspektif al-Qur’an) - Novi Heryanti, Nuraini (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2019)
The practice carried out by the Kluet community regarding adoption of children is generally good, in which it is worth Sadaqah, maintaining silaturrahmi, aiming to help fellow Muslims, and maintaining a strong brotherhood among fellow Muslims both adopted children because of child leaves, tribal children, senamo, call children, according with Islamic teachings. But with regard to adoption of children due to the couple not having children, then living with foster siblings, there are some things that are not appropriate with the teachings of Islam, which is related to the issue of the status or status of the adopted child. In practice, a part of the Kluet community that adopts their status is like their own biological children, this can be seen from the Family Card and school report cards by using the name of their adopted parents in the child's identity. In relationships mahrampun socially sometimes less attention to the limitations of relationships and genitalia in the family. This is because they consider their adopted children like biological children. Likewise in the matter of marriage, in the adopted family the Kluet community still attaches great importance to emotional ties so that if anyone gets married they will feel ashamed.Â